The role of the teacher concerning the Holy Scripture lesson in the courses of Bulgarian language and literature (High School level) - Spassov, Chavdar (Forum Theologicum Sardicense, 2025)
Chavdar Spassov, The role of the teacher concerning the Holy Scripture lesson in the courses of Bulgarian language and literature (High School level). The changing conditions in contemporary society are leading to significant alterations in the role of teachers in the process of teaching and educating students. This article outlines the main moral aspects of this issue and emphasizes the need for a new teaching methodology that strengthens the correlation between “faith” and “life.” It also considers the most important goals and tasks of teaching Holy Scripture within Bulgarian language and literature courses at the high school level, as well as the necessity for methodical planning of individual lessons.